(untitled) - Komiya, Ryutaro (Tokyo, 1990)
Collection of the author's essays previously published in Japanese or English between 1975-1989 about trade, industry, and government in Japan
Keywords: Industries,Industrial policy,Ngành công nghiệp,Chính sách công nghiệp; Japan,Nhật Bản,Nhật Bản